2022
DOI: 10.14423/smj.0000000000001435
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Sex and Gender Minority Standardized Patients into a Workshop on Gender-Inclusive Patient Care: Exploring Medical Student Perspectives

Abstract: Objectives: Sexual and gender minority (SGM) communities experience significant health disparities. Although coverage of health issues specific to these communities has increased in the undergraduate medical curriculum, there is still opportunity for improved teaching about sexual diversity and inclusive care. The goal of this study was to assess students' perceptions of and satisfaction with a half-day workshop focused on sexual history taking and transgender health. Methods:The second-year clinical skills co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…This review found that certain competencies in the report are being addressed in these efforts to enhance LGBTQ+ medical education. Specifically, a competency that was addressed across many studies within the domain of patient care describes the expected ability for graduating students to obtain an inclusive sexual history, ‘Sensitively and effectively eliciting relevant information about sex anatomy, sex development, sexual behavior, sexual history, sexual orientation, sexual identity, and gender identity from all patients in a developmentally appropriate manner.’[ 4 ] This competency was addressed by 13 interventions in this literature review [ 20 , 23 , 31 , 43 , 46–48 , 62 , 66 , 82 , 84 , 88 , 94 ]. However, there remains work to be done in this field in order to fully address all recommended competencies.…”
Section: Discussionmentioning
confidence: 99%
“…This review found that certain competencies in the report are being addressed in these efforts to enhance LGBTQ+ medical education. Specifically, a competency that was addressed across many studies within the domain of patient care describes the expected ability for graduating students to obtain an inclusive sexual history, ‘Sensitively and effectively eliciting relevant information about sex anatomy, sex development, sexual behavior, sexual history, sexual orientation, sexual identity, and gender identity from all patients in a developmentally appropriate manner.’[ 4 ] This competency was addressed by 13 interventions in this literature review [ 20 , 23 , 31 , 43 , 46–48 , 62 , 66 , 82 , 84 , 88 , 94 ]. However, there remains work to be done in this field in order to fully address all recommended competencies.…”
Section: Discussionmentioning
confidence: 99%